It's elementary, my dear watson: Time-optimal sorting algorithms on a completely overlapping network - Kantabutra S. (2014)
Several parallel architectures exist in computer science literature. Motivated by the experimental overlapping connectivity network, we propose a new theoretical network called a completely overlapping network (CON). This network is an extension of the overlapping connectivity network with multiple buses. In this paper we investigate some properties of this network and demonstrate the use of CON and its usefulness by solving two toy problems: decimal number and one-digit binary number sortings. © Springer-Verlag Berlin Heidelberg 2005.